“Thou shalt bid thy fair hands rove”: L. E. L.’s Wooing of Sex, Pain, Death and the Editor - Lawford, Cynthia (Romanticism on the Net)

(untitled) (Université de Montréal, 2003)
AbstractSo what if Letitia Landon had three illegitimate children by William Jerdan? What difference does the discovery of the affair make for our reading of L. E. L.’s poetry? This essay begins to explore these questions with regard to her love poems, many of which culminate in a desire for death even greater than that voiced for the absent beloved. We have been disinclined to believe in the authenticity of the poems’ fatal passions and naturally require more evidence before we can assume that any of their intensity is related to Landon’s feelings for the bibulous Literary Gazette editor. Through examining a number of Landon’s early, sexually daring poems and her relationship with Jerdan at the time of their writing, this essay provides some of that evidence and discusses the part these works likely played in the evolution of this literary and sexual relationship. According to Landon’s theory, genius had to devote its grand soul to an inferior being to experience the torment essential for producing literary works of the highest order. Landon viewed her affair with the editor as a means to a greater end: the poems themselves, including, not incidentally, their publication and promotion.